2019
DOI: 10.1089/ars.2018.7555
|View full text |Cite
|
Sign up to set email alerts
|

AanatKnockdown and Melatonin Supplementation in Embryo Development: Involvement of Mitochondrial Function and DNA Methylation

Abstract: Aims: In addition to pineal gland, many cells, tissues, and organs also synthesize melatonin (N-acetyl-5methoxytryptamine). Embryos are a group of special cells and whether they can synthesize melatonin is still an open question. However, melatonin application promoted embryo development in many species in in vitro condition. The purpose of this study was to investigate whether embryos can synthesize melatonin; if it is so, what are the impacts of the endogenously produced melatonin on embryo development and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 86 publications
0
24
0
Order By: Relevance
“…With the use of a protein degradation procedure, Suofu et al (39) deduced that the SNAT was located in the matrix of mitochondria; they claimed that melatonin was synthesized exclusively in the matrix of mitochondria. In contrast, Yang et al observed that the SNAT was present in the mitochondrial intermembrane space close to the outer membrane (42). This seems to support the observations of Kerenyi et al (43,44) that SNAT product was observed in the mitochondrial intermembrane space of pinealocytes.…”
Section: Fig 2 Localization Of Snat In Rat Choroid Plexus Endothelimentioning
confidence: 63%
“…With the use of a protein degradation procedure, Suofu et al (39) deduced that the SNAT was located in the matrix of mitochondria; they claimed that melatonin was synthesized exclusively in the matrix of mitochondria. In contrast, Yang et al observed that the SNAT was present in the mitochondrial intermembrane space close to the outer membrane (42). This seems to support the observations of Kerenyi et al (43,44) that SNAT product was observed in the mitochondrial intermembrane space of pinealocytes.…”
Section: Fig 2 Localization Of Snat In Rat Choroid Plexus Endothelimentioning
confidence: 63%
“…Serum melatonin of pregnant women gradually increases in the course of gestation, especially during the third trimester of pregnancy, and reaches its peak at the time of delivery [ 232 , 233 ]. Since trophoblast [ 234 ] and placenta [ 235 , 236 ], as well as embryo [ 237 , 238 ] and stages of the fetus have the capacity to synthesize melatonin, the melatonin of pregnant women is probably derived from the mother, fetus, and placenta as a whole. Thus, pregnant women have a significantly elevated serum melatonin level, which is approximately twice as high as that of control subjects or even higher [ 181 ].…”
Section: The Outcomes Of Covid-19 Are Potentially Linked To Melatomentioning
confidence: 99%
“…MT regulates the earliest stages of intrauterine growth in mice [ 15 ]. Interestingly, it was shown that AANAT is mostly located in mitochondria of embryonic cells.…”
Section: Melatonin Synthesis and Signaling Ways Of Embryogenesismentioning
confidence: 99%
“…Pineal MT regulates embryo and fetal development [ 14 ]. However, melatonin is produced in the mammalian embryo, within the mitochondria of the embryo [ 15 ]. Although requiring confirmation in future studies, including in human embryos, such data is challenging to the sole role of maternal, pineal MT in the regulation of fetal development.…”
Section: Introductionmentioning
confidence: 99%